Tuning the magnetic states in AA-stacked bilayer zigzag graphene nanoribbons - Prayitno, Teguh Budi (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2022)
Available reports mentioned that the magnetic ground state in the AA-stacked bilayer zigzag graphene nanoribbons is the non-magnetic state. As a consequence, it is impossible to exploit magnetism for future electronic devices. This paper aims to show how to generate magnetism in the AA-stacked bilayer zigzag graphene nanoribbons by employing ?rst-principles calculations. As we stacked different ribbon widths, the magnetic ground states appeared for all the thicknesses. In general, the G-type antiferromagnetic state, which is the antiferromagnetic alignment between both intraplane- and interplane-edge carbon atoms, is the ground state for all the thicknesses. We also found that the degenerate magnetic ground states and excited states may appear under certain thicknesses, thus yielding the richness of the magnetic state. As hole-electron doping was applied, a phase transition of magnetic ground state emerged for certain thicknesses, indicating that a new magnetic ground state in the AA-stacked bilayer zigzag graphene nanoribbons can be tuned by the doping.